BUSINESS FEASIBILITY AND CULTIVATION MANAGEMENT OF BROILER UNDER PARTNERSHIP SCHEME - Wantasen, Erwin; S. J. K. Umboh; J. R. Leke; F. N. Sompie (IJRDO - Journal of Business Management, 2019)
This study goals to investigate business feasibility of broiler cultivation under partnership scheme between plasma breeders and PT Charoen Pokphan Jaya Farm, in the Sub-district of Kalawat, District of North Minahasa, Province of North Sulawesi, and acknowledge cultivation management, income, and Break Even point value. Thus, the site of research was employed purposive method. While, selection method of respondents, as sample, was done by census sampling against 15 plasma breeders. As a result, this research finds that partnership scheme of plasma breeders and PT Charoen Pokphan Jaya Farm was Public Main Company (PIR). Reasonably, this was used since it was beneficially profitable in capital fulfillment for plasma breeders, where the main company provided production facility of husbandry and marketing insurance. Further, Break Even Point (BEP) within a unit was 6,599,03 kilograms, and breeders’ averagely production mean was 8,275 kilograms. While, BEP (in Rupiah) was Rp. 14,350 /kg and its breeders’ average sales was Rp. 17,822 /kg. In sum up, it shows that broiler business under partnership scheme performed by PT Charoen Pokphan Jaya Farm in the Sub-district of Kalawat had reached its BEP unit and BEP in Rupiah. The gross B/C value of broiler cultivation was 1,32. According to economic analysis, income, the measurement of BEP and gross B/C can be concluded that partnership scheme of broiler in the Sub-dstrict of Kalawat, District of North Minahasa was beneficially profitable and feasible to be developed further.